Aislamiento, selección e identificación de una Cepa de Alta Producción de Alcohol a partir de la Elaboración de Cerveza de Quinua (chenopodium quinoa). - Cordonez Suntasig, Kleber Trajano (2018)
This research work had as main objective isolate, select and identify a stump of high alcohol production from the elaboration of quinoa beer (Chenopodium quinoa) in a farming medium (sabouraud dextrosa), where it was determined that the sediment contains different type of yeast at the end of the alcoholic fermentation of the beer. The product was packaged in three different sterilized containers, the first contained sediments of the upper part, the second contained sediments of the middle part and the third contained sediments of the lower part, where is the most part of yeast, through the corresponding trials about the topic, it was possible to identify that the alcoholic strain is of genus “Saccharomyces” coming from the fermentation of the quinoa beer. The isolated biomass, selected and identified from the best treatment in the analysis of the organoleptic characteristics, variable responses that were used (% alcohol, color, smell and outline). The experimental part had a duration of 30 days, in which the elaboration of the beer was carried out, fermentation of it and the isolation, selection and identification of the alcoholic strain. A medium of general cultivation was used since in research the best medium for development is the (Sabouraud dextrosa) in the first isolation is where the 6 best colonies were selected, which were reseeded to obtain pure strains, was applied to different temperatures and growth times, once the time elapsed, the one with the highest percentage of alcohol was selected to obtain biomass of the alcoholic strain of the genus Saccharomyces. It was determined that among the commercial yeast the cost is higher and the yeast obtained the cost is lower both in the preparation and in the presentation in the market, as for the fermentation the obtained yeast is of greater fermentation and the time of action was reduced.